Nilai-Nilai filosofis dalam Karakter Tokoh Wayang Semar Perspektif Pendidikan Masyarakat Hindu Jawa di Pringsewu Lampung - oke Setiawan (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2018)
ABSTRACTLack of understanding of philosophical values in Semar puppet characters, which makes the decline of the noble values of Javanese people today. So that got the formulation of the problem, who is the character of the semar puppet in Javanese wayang, the philosophical value of the puppet semar character and its relevance to the Javanese Hindu community in Pringsewu Lampung. This research is a descriptive research (descriptive research) using the descriptive field method. This study tries to explore how the semar and philosophical values of the Wayang Semar characters, namely, eat the name Semar. Semar is a puppet character who gives a toadan like a teacher. the meaning of the Wayang Semar form which is a picture of God or the balance of life to reach God. The origin of the Semar puppet is interpreted as the concept of morality in Hinduism. The philosophical value of Semar is as a teacher who always gives enlightenment to care for the warriors to always be on the path of dharma. and its relevance to the education of the Javanese Hindu Community in Pringsewu Lmpung. Wisdom value, the value of Tri Hita Krana and Education as servants. All of them are concepts from the philosophical character of the character Semar. Keywords: Philosophical Value, Character, Semar Character, Education